Answer:
1) n = - 7 2) n = 2
Explanation:
1)
-4(n-7)+4n=-8-3(n-5) Let's multiply it out
-4*n - 4* (-7) + 4n = - 8 - 3*n -3 * (- 5)
-4n + 28 + 4n = - 8 -3n +15 Combine like terms
-4n + 4n + 28 = -8 + 15 - 3n
28 = 7 - 3n Subtract 7 from each side
28 - 7 = 7 - 7 - 3n
21 = - 3n Divide each side by -3
21 / -3 = - 3n / -3 -3 cancels on the right
21 / -3 = n
- 7 = n
2)
4(-8n+10)+4(4n-4)= -6n+2n Multiply it out
4 * - 8n + 4 * 10 + 4 * 4n + 4 * (-4) = - 6n + 2n
- 32n + 40 + 16n - 16 = - 6n + 2n Combine like terms
- 32n + 16n + 40 - 16 = - 6n + 2n
- 16n + 24 = - 4n Add 16n to each side
- 16n + 16n + 24 = - 4n + 16n
24 = 12n Divide each side by 12
24/12 = 12n/12 12 cancels on the right
24/12 = n
2 = n